POTENSI MIKROALGA SEBAGAI SUMBER BIOMASA DAN PENGEMBANGAN PRODUK TURUNANNYA - Noer, Abyor Handayani; Dessy, Ariyanti (TEKNIK, 2012)
The first use of microalgae by humans as food detected in the dates back 2000 years, but the development ofbiotechnology of microalgae just began in the middle of this century. Microalgae refer to biomass resourcecontain many useful components such as protein, carbohydrate, fatty acid, etc. Products based microalgae arediverse from human food and nutrition, animal feed and nutrition up to fine chemicals such as triglycerideswhich is able to be converted to biodiesel. Microalgae is a promising biomass resources, (i) microalgae isrenewable resources which has high biodiversity properties, (ii) production cost of converting process frommicroalgae biomass into its derivatives relatively low, (iii) product derivatives of microalgae have a highdemand in market. Based on above, microalgae can be developed further to be applied as raw material for food,energy and pharmacy. This paper described microalgae in general and the developing technology used toproduce commercial microalgae based product.